2016
DOI: 10.5194/bg-13-4581-2016
|View full text |Cite
|
Sign up to set email alerts
|

Key biogeochemical factors affecting soil carbon storage in <i>Posidonia</i> meadows

Abstract: Abstract. Biotic and abiotic factors influence the accumulation of organic carbon (C org ) in seagrass ecosystems. We surveyed Posidonia sinuosa meadows growing in different water depths to assess the variability in the sources, stocks and accumulation rates of C org . We show that over the last 500 years, P. sinuosa meadows closer to the upper limit of distribution (at 2-4 m depth) accumulated 3-to 4-fold higher C org stocks (averaging 6.3 kg C org m −2 ) at 3-to 4-fold higher rates (12.8 g C org m −2 yr −1 )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 65 publications
3
47
1
Order By: Relevance
“…As a general trend, estimates of long-term SAR derived from 14 C in soils are lower than short-term SAR derived from 210 Pb (Baskaran et al, 2016). For example, Serrano, Ruhon, et al (2016), Serrano, Ricart, et al (2016) reported 14 C-based SAR 1.2 to 4 times less than 210 Pb-based SAR ( Table 2). Discrepancies between 14 C-and 210 Pb-based SAR are also reported in unvegetated soils (Baskaran et al, 2016).…”
Section: Centennial Ratesmentioning
confidence: 93%
See 1 more Smart Citation
“…As a general trend, estimates of long-term SAR derived from 14 C in soils are lower than short-term SAR derived from 210 Pb (Baskaran et al, 2016). For example, Serrano, Ruhon, et al (2016), Serrano, Ricart, et al (2016) reported 14 C-based SAR 1.2 to 4 times less than 210 Pb-based SAR ( Table 2). Discrepancies between 14 C-and 210 Pb-based SAR are also reported in unvegetated soils (Baskaran et al, 2016).…”
Section: Centennial Ratesmentioning
confidence: 93%
“…The slices were then ground in an agate mortar and subdivided for analysis. All depths were corrected for compression considering a uniform distribution of the compaction throughout the total length of the cores as described by Serrano, Ricart, et al (2016). The mean ± SE compression factors (depth ratios between compressed and uncompressed soils) were 1.05 ± 0.18, 1.04 ± 0.03, and 1.16 ± 0.11 in the cores from sabkha, mangrove, and seagrass sites of the Arabian Gulf, respectively, and 1.19 ± 0.14 and 1.23 ± 0.17 in the seagrass and mangrove cores of the Red Sea.…”
Section: Biogeochemical Analysismentioning
confidence: 99%
“…Furthermore, there is undoubtedly an important interaction between the hydrodynamic environment and sediment grain size, with greater percentages of fine sediments typically found in more sheltered sites (Mazarrasa et al, 2017a). Sediment grain size likely plays a role in controlling the amount of carbon stored in eelgrass sediments, as finer sediments are found to contain higher proportions of organic carbon (Dahl et al, 2016;Mazarrasa et al, 2018;Serrano et al, 2016). In Southeast Alaska, we found a positive relationship between OC content and a qualitative measure of sediment grain size (R 2 = 0.47, p = 0.004), suggesting that sites with sediments classified as mud or sandy mud tended to have higher %OC ( Figure S2a).…”
Section: Drivers Of Variability In Blue Carbon Parametersmentioning
confidence: 99%
“…For example, the Verified Carbon Standard includes default carbon sequestration values for marsh and mangrove ecosystems, whereas default values for seagrass systems were identified as a "key science and policy research need" (Needelman et al, 2018). This is not surprising considering that there are 72 species of seagrasses worldwide (Short et al, 2011), the carbon dynamics of which are modulated by a wide range of biological and physical factors such as plant size, seagrass characteristics (e.g., density, canopy height, root-rhizome structure), hydrodynamic conditions (e.g., exposure, depth, wave height), and sediment characteristics (e.g., sediment grain size, bulk density, porosity; Dahl et al, 2016;Mazarrasa et al, 2018;Rozaimi et al, 2013;Samper-Villarreal et al, 2016;Serrano et al, 2014Serrano et al, , 2016. In addition to global and regional variation in seagrass blue carbon storage, large variability has been observed at the local scale-within meadows-further emphasizing the need for local-level data on species specific carbon stocks and sequestration rates (Oreska et al, 2017;Prentice et al, 2019;Ricart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of seagrass meadows to bury and preserve archaeological artefacts is influenced by interactions of biological factors such as growth pattern, meadow productivity, cover and density, chemical factors such as recalcitrance of seagrass debris and physical factors such as water depth, hydrodynamic energy and soil accumulation rates (Serrano et al 2016b). Large and long-living seagrass meadows of the genera Posidonia and Thalassia can build organic-rich deposits several meters in thickness in certain habitats (Mateo et al 1997;Lo Iocano et al 2008;Duarte et al 2013), while opportunistic and/or low biomass seagrass meadows of the genera Halophila and Zostera do not build similarly thick sediments.…”
Section: Seagrass Sediment Deposits As Security Vaults Of Underwater mentioning
confidence: 99%